KAT8 Knockdown Reverses hucMSC Senescence and Enhances Diabetic Wound Healing Efficacy - Chen, Ruijing; Zhang, Xiaoyue; Chen, Jun (Experimental and Clinical Endocrinology & Diabetes, 2025)
The histone acetyltransferase KAT8 has been implicated in stem cell biology, but its specific role in human umbilical cord mesenchymal stem cells (hucMSCs) senescence and therapeutic efficacy for diabetic wounds is unclear. This study aimed to investigate the role of KAT8 in hucMSC senescence and to determine if KAT8 knockdown could reverse senescence and enhance the efficacy of hucMSCs in promoting diabetic wound healing. hucMSCs were extracted from the umbilical cord, and senescence was induced. KAT8 expression was assessed in senescent and non-senescent hucMSCs. Senescence markers (senescence-associated β-galactosidase [SA-β-gal] staining, P16, P21 expression), proliferation (Cell Counting Kit-8 [CCK-8], colony formation), cell migration (cell scratch), and differentiation potential (alizarin red and oil red O staining) were evaluated in vitro. Western blotting and quantitative polymerase chain reaction were performed to detect protein expression and mRNA expression levels, respectively. For in vivo studies, a type 1 diabetes mellitus mouse wound healing model was established. Mice received local injections of phosphate-buffered saline (PBS), hucMSCs transduced with a negative control vector (NC hucMSCs), or KAT8-knockdown hucMSCs. Wound closure rates were monitored, and histological analyses (Hematoxylin and eosin [H&E], Masson staining). KAT8 expression decreased during hucMSCs senescence. Knockdown of KAT8 downregulated senescence-associated genes (e.g., P21 and P16) while enhancing hucMSCs proliferation, migration, and survival without altering surface stem cell marker expression. In vivo experiments further confirm that KAT8-knockdown hucMSCs significantly promoted wound healing in a type 1 diabetic mouse model, exhibiting superior therapeutic efficacy.Knockdown of KAT8 effectively reverses senescence in hucMSCs and enhances their therapeutic potential for diabetic wound healing.
Keywords: KAT8; mesenchymal stem cells; senescence; epigenetic modification; wound healing; diabetic